ANALISIS KUALITAS MINYAK GORENG BERDASARKAN NILAI GRADIEN PERUBAHAN SUDUT POLARISASI MENGGUNAKAN METODE ELEKTROOPTIS - Ekasari Ekasari; Ketut Sofjan Firdausi (Youngster Physics Journal, 2016)
Palm cooking oil quality testing has been done using natural polarization and electro-optics. Tests conducted to determine the quality of oil based active optical properties of the oil. The addition of external electric field aims to get the value of the polarization angle changes each brand oil. Oil samples were tested in the form of palm oil with a variety of brand new and has ditreatmen oil for frying foodstuffs. Test parameters after the addition of external electric field gradient that is of value elektrooptis. The test results, samples of oil to the value of large polarization angle gradient changes indicated have relatively low quality. Instead gradient small polarization angle, indicating high quality oil. Elektrooptis smallest gradient value of 0,51o/ kV, while the largest gradient value is 0,68o / kV. Keywords: polarization, elektrooptis, oil quality